Improving Grade 7 Students’ Reading Comprehension Ability Using the 12PBL Learning Management - Pratin Sawasri; Suarsaraha Suwannathep; Autthapon Intasena; Thussaneewan Srimunta (Journal of Educational Issues, 2024)
The purposes of the study were 1) to study the effects of the 12PBL technique learning management on Grade 7 students’ reading comprehension; and 2) to study students’ satisfaction with learning in the 12PBL technique. The samples were 22 Grade 7 students in a school in Thailand selected by a purposive sampling method. The instruments were the 12PBL learning management plan, a learning achievement test for reading comprehension, and a satisfaction questionnaire for the 12PBL learning management. The effectiveness of the 12PBL learning management plans was assessed using the effectiveness index (E1/E2) with the determining criteria of 80/80 and a paired-sample t-test. Mean scores, percentages, and standard deviation were used to analyze the questionnaire data. The results of the study show that the 12PBL technique could be considered an alternative solution for fixing reading comprehension problems. Moreover, the instructional technique also brought about satisfactory learning in a language classroom.